2007
DOI: 10.1783/147118907780254277
|View full text |Cite
|
Sign up to set email alerts
|

Pressed for time: providing the Standard Days Method and oral contraceptives in India

Abstract: Many of this Journal's older readers will be familiar with the Oxford-Family Planning Association (Oxford-FPA) contraceptive study and will, indeed, have made important contributions to data collection. Accordingly, I was delighted that the Journal Editor had chosen the most recent publication from the study 1 as the subject for a Journal Review. I am also grateful to Dr Mills for taking so much trouble to produce a succinct summary of a complex paper. 2 There are, however, one or two points about the review t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…However, some of the providers had complained that the SDM necessitated time-consuming counselling sessions. Studies conducted in India (SDM 10 minutes vs Pill 8 minutes),17 Rwanda (SDM 44 minutes vs Pill 38 minutes)18 and Peru (SDM 23 minutes vs Pill 15 minutes)19 demonstrated that the SDM can be offered with a similar length counselling session as required for the oral contraceptive pill. The amount of time needed to counsel new SDM users typically did not exceed what is generally allocated in respect of new family planning consultations 10.…”
Section: Discussionmentioning
confidence: 99%
“…However, some of the providers had complained that the SDM necessitated time-consuming counselling sessions. Studies conducted in India (SDM 10 minutes vs Pill 8 minutes),17 Rwanda (SDM 44 minutes vs Pill 38 minutes)18 and Peru (SDM 23 minutes vs Pill 15 minutes)19 demonstrated that the SDM can be offered with a similar length counselling session as required for the oral contraceptive pill. The amount of time needed to counsel new SDM users typically did not exceed what is generally allocated in respect of new family planning consultations 10.…”
Section: Discussionmentioning
confidence: 99%
“…In Peru, according to simulated clients trained to choose the medroxyprogesterone acetate injectable (DMPA) in the consultation, 84% of providers correctly told clients that menstruation might stop, but only 15% mentioned that temporary infertility might follow discontinuation of the method (León, Monge, Zumarán, García, & Ríos, 2001). Provider deficiencies in implementing service guidelines have been documented for the most frequently used methods-sterilization (Visaria, 1999), intrauterine devices (IUDs; Viberga, Odlind, & Zodzika, 2006), pills (Kim et al, 1998;León, Ríos, & Zumarán, 2005), and injectables (León et al, 2001), as well as emergency contraception (Ngoc, Ellertson, Surasrang, & Loc, 1997) and the Standard Days Method (León, Arévalo, et al, 2007;León, Lundgren, Huapaya, Jha, et al, 2007).…”
mentioning
confidence: 99%